A Critical Evaluation of Equivalence in Translation Theories - Agsebat , Halah; Elarafi, Nora (مجلة كلية الاداب, 2024)
The concept of equivalence can be assumed to hold a central position in translation studies. However, it has been controversial, causing many heated debates among scholars of translation studies according to its nature, definition and applicability. This research paper provides a critical evaluation of the most influential equivalence theories that have been proposed by scholars in the field, such as Vinay and Darbelnet (1958), Jakobson (1959), Nida and Taber (1969), Catford (1965), House (1997), Koller (1979), Newmark (1981), Baker (1992), and finally, Pym (2010). These theories are presented in order to provide a better understanding of how the concept of equivalence developed. It is concluded that the concept of equivalence in the translation process varies among translation scholars according to their view on the qualities of equivalence.